Investigation of hydrolysis of olmesartan medoxomil in different pH buffers by simultaneously measuring olmesartan medoxomil and olmesartan - Lauren Landry; Xiaowei Dong (PLoS ONE, 2025)
Olmesartan medoxomil (OLM) is an ester prodrug of olmesartan (OL) developed to overcome the poor permeability of OL. OLM is an angiotensin receptor blocker and is commonly used to treat hypertension. However, OLM has low water solubility and low bioavailability of 26%. It is understood that OLM is unstable in aqueous media; however, this hydrolysis has not been specifically studied in a way that has produced reliable, publishable data. Previously published analytical methods tend to focus mainly on quantitative measurement of OLM, but not quantitative measurement of OL. The objective of this study was to investigate the solubility and aqueous hydrolysis of OLM in different pH buffers by developing an analytical method for the simultaneous measurement of OLM and OL. A novel HPLC method was developed and validated to simultaneously quantify OLM and OL. The solubility of OLM was pH-dependent 37°C, which could lead to food effects and precipitation of OLM in the small intestine. The aqueous hydrolysis of OLM was rapid and significant and followed the zero-order kinetic model with different hydrolysis rates varying across different pH levels in the order: pH 1.2 < pH 3.5 < pH 4.6 ≈ pH 6. These findings indicate that, in addition to low water solubility, aqueous hydrolysis in the gastrointestinal tract contributes to OLM’s low bioavailability. The study emphasizes the importance of fully understanding the solubility and hydrolysis of ester-based prodrugs. Strategies that protect OLM from hydrolysis could have the potential to enhance its bioavailability. Considering ester prodrugs are a key strategy to improve bioavailability, our study in this manuscript is significant for drug formulation development.